BATAS USIA PERKAWINAN MENURUT FUKAHA DAN PENERAPANNYA DALAM UNDANG-UNDANG PERKAWINAN DI DUNIA MUSLIM - Asrori, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2015)
Abstract: Marriage Age Limit According to Fuqaha and Its Application in the Marriage Law in the Islamic World. This article reviews the opinions of the Islamic scholars on the minimum age of marriage and its application in marriage law in some Islamic countries. The fuqaha (jurists) have different opinion on the age limit for someone to be called puberty. According to Hanafi scholars, a boy reaches his puberty at 18 years of age and girl at 17 years. Shafi’i schoolars limit of 15 years for a boy and 9 years for a girl. Hanbali, both men and women 15 years of age. While the Mâliki mark of maturity with hair growth in some places/limb. The differences of opinion on the concept of puberty have resulted dissimilarity in the minimum age for marriage in Muslim countries.Abstrak: Batas Usia Perkawinan Menurut Fukaha dan Penerapannya dalam Undang-Undang Perkawinan di Dunia Islam. Artikel ini mengulas pendapat para ulama mazhab tentang batas minimum usia menikah dan penerapannya dalam hukum perkawinan di beberapa negara Islam. Di dalam kitab-kitab fikih, para fukaha berbeda pendapat tentang batasan usia seseorang untuk dapat disebut baligh. Menurut ulama Hanâfi, anak laki-laki dipandang baligh apabila usianya telah mencapai 18 tahun dan perempuan 17 tahun. Mazhab Syâfi’i memberikan batas 15 tahun untuk laki-laki dan 9 tahun untuk perempuan. Hanbali, baik laki-laki dan perempuan 15 tahun. Sedangkan ulama Mâliki menandai kedewasaan dengan tumbuhnya rambut di beberapa tempat/anggota tubuh. Perbedaan pendapat mengenai konsep baligh ini mengakibatkan